Ecological Life History of Baetisca Berneri Tarter and Kirchner From a West Virginia Stream (Ephemeroptera: Baetiscidae) - William R. Morris; Dwight L. Chaffee; Donald C. Tarter (Psyche: A Journal of Entomology)
The primary objective of this investigation was to study the ecological life history of the mayfly Baetisca berneri Tarter and Kirchner in Laurel Fork, Mingo Co., West Virginia. Many authors, including Say (1839), Traver (1931), Needham et al. (1935), Berner ( I940, 1955 ), Edmunds (I 960), Schneider and Berner (1963), Pescador and Peters (1971, 1974), Lehmkuhl (1972), Tarter and Kirchner (1978) and Chaffee and Tarter (1979), have reported studies on the taxonomy and ecology of the genus Baetisca.